LISA Pathfinder: Mission and status - Antonucci, F; Armano, M; Audley, H; Auger, G; Benedetti, M; Binetruy, P; Boatella, C; Bogenstahl, J; Bortoluzzi, D; Bosetti, P; Caleno, M; Cavalleri, A; et al. (2011)
LISA Pathfinder, the second of the European Space Agency's Small Missions for Advanced Research in Technology (SMART), is a dedicated technology demonstrator for the joint ESA/NASA Laser Interferometer Space Antenna (LISA) mission. The technologies required for LISA are many and extremely challenging. This coupled with the fact that some flight hardware cannot be fully tested on ground due to Earth-induced noise led to the implementation of the LISA Pathfinder mission to test the critical LISA technologies in a flight environment. LISA Pathfinder essentially mimics one arm of the LISA constellation by shrinking the 5 million kilometre armlength down to a few tens of centimetres, giving up the sensitivity to gravitational waves, but keeping the measurement technology: the distance between the two test masses is measured using a laser interferometric technique similar to one aspect of the LISA interferometry system. The scientific objective of the LISA Pathfinder mission consists then of the first in-flight test of low frequency gravitational wave detection metrology. LISA Pathfinder is due to be launched in 2013 on-board a dedicated small launch vehicle (VEGA). After a series of apogee raising manoeuvres using an expendable propulsion module, LISA Pathfinder will enter a transfer orbit towards the first Sun-Earth Lagrange point (L1). After separation from the propulsion module, the LPF spacecraft will be stabilized using the micro-Newton thrusters, entering a 500 000 km by 800 000 km Lissajous orbit around L1. Science results will be available approximately 2 months after launch. © 2011 IOP Publishing Ltd.